The Failure of the Zulkifli Nurdin Dynasty in the Case of Ratu Munawaroh's Defeat in the 2020 Jambi Gubernatorial Election - Seprini, Giyanti Elsa; Wardani, Sri Budi Eko (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research explains the phenomenon of the failure of Zulkifli Nurdin's political dynasty, who had held power in Jambi Province since 1999. More specifically this research aims to analyze the reasons behind the defeat of Ratu Munawaroh (Zulkifli Nurdin's wife) in the 2020 Jambi gubernatorial election. Researchers used a qualitative study and boundary control theory from Edward L. Gibson (2012) with two frameworks, namely: boundary strengthening by political dynasties to maintain power in an area and boundary opening by the opposition to open the boundaries of political dynasty power.This research found that; in the case of Ratu Munarawoh's defeat, boundary strengthening did not take place (passive family support, difficulty in getting PAN support, and economic problems) which led to the strengthening of boundary opening (Al Haris-Abdullah Sani won PAN support, Ratu Munawaroh was the target of negative and anti-dynasty campaigns)